2012
DOI: 10.1007/s13402-011-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal adenoma to carcinoma progression is accompanied by changes in gene expression associated with ageing, chromosomal instability, and fatty acid metabolism

Abstract: BackgroundColorectal cancer develops in a multi-step manner from normal epithelium, through a pre-malignant lesion (so-called adenoma), into a malignant lesion (carcinoma), which invades surrounding tissues and eventually can spread systemically (metastasis). It is estimated that only about 5% of adenomas do progress to a carcinoma.AimThe present study aimed to unravel the biology of adenoma to carcinoma progression by mRNA expression profiling, and to identify candidate biomarkers for adenomas that are truly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 73 publications
5
49
0
1
Order By: Relevance
“…Our network analysis attributed 82.9% of the genes to one of the Early trajectories, and only 13.4% were attributed to a Late trajectory. This result indicates that the adenoma-carcinoma transition incorporated a relatively small amount of specific changes, a finding that is in agreement with previous results (5,6).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our network analysis attributed 82.9% of the genes to one of the Early trajectories, and only 13.4% were attributed to a Late trajectory. This result indicates that the adenoma-carcinoma transition incorporated a relatively small amount of specific changes, a finding that is in agreement with previous results (5,6).…”
Section: Discussionsupporting
confidence: 93%
“…However, this study looked at the end point of carcinogenesis, the colon adenocarcinoma itself, and the question remains at what stage in carcinogenesis these pathways exert their effect. Only few studies have looked at the temporal dynamics of colon cancer progression, but even those studies were limited to the normal to adenoma transition or the adenoma to carcinoma transition (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, studies have clearly shown that genetic/ epigenetic changes may greatly affect the development of the disease transforming the epithelial cells into adenocarcinomas (Frank et al, 2010;Carvalho et al, 2012;Sinha et al, 2013;Farkas et al, 2014). Numerous signs and symptoms have been reported in patients presenting with CRC and a host of attributable factors have been found to play a significant role in the development of this disease.…”
Section: Discussioncmentioning
confidence: 99%
“…A complex interplay of multiple environmental and genetics factors is involved in the pathogenesis of CC, although the interactions of such events may vary from one individual to another (Goel and Boland, 2010). From a pathological standpoint, rhe development of CC is characterized by a sequence of events during which normal colonic epithelium gradually transforms to carcinoma tissue, in most cases via the development of colorectal adenomas (Brenner et al, 2007;Carvalho et al, 2012). This sequence of events seems to be driven by an accumulation of molecular alterations causing progressive disorders in cell growth, differentiation, and apoptosis (Sugai et al, 2003;Carvalho et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From a pathological standpoint, rhe development of CC is characterized by a sequence of events during which normal colonic epithelium gradually transforms to carcinoma tissue, in most cases via the development of colorectal adenomas (Brenner et al, 2007;Carvalho et al, 2012). This sequence of events seems to be driven by an accumulation of molecular alterations causing progressive disorders in cell growth, differentiation, and apoptosis (Sugai et al, 2003;Carvalho et al, 2012). Genetic factors are believe to play a major role in colorectal carcinogenesis (Fearon, 2011;Armaghany et al 2012).…”
Section: Introductionmentioning
confidence: 99%